2019
DOI: 10.1021/acs.orglett.9b01469
|View full text |Cite
|
Sign up to set email alerts
|

Direct Access to β-Trifluoromethyl-β-hydroxy Thioesters by Biomimetic Organocatalytic Enantioselective Aldol Reaction

Abstract: A broadly applicable biomimetic enantioselective decarboxylative catalytic aldol reaction of trifluoromethyl ketones with malonic acid half-thioesters (MAHTs) is described. Utilizing cinchona-based thioureas as highly efficient polyketide synthase-mimic catalysts, chiral tertiary aldols, β-trifluoromethyl-β-hydroxy thioesters, were obtained in up to 99% yield and 95% ee. Facile transformation of the thioester moiety of the aldol adducts showcases the synthetic utility of this biomimetic aldol protocol to deliv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…[10] The Song group reported an asymmetric decarboxylative aldol reaction of malonic acid half-thioesters 1 (MAHTs) with trifluoromethyl ketones 17 catalyzed by a cinchonidine derived thiourea catalyst F to give enantioenriched β-CF 3 -β-hydroxy esters 18 (Scheme 9) bearing trifluoromethylated tertiary carbon center in low to excellent yields (3-99 %) and with good to excellent enantioselectivities (50-95 % ee). [11] The authors screened several MAHTs, out of which para-fluorophenyl substituted MAHT was found to be most suitable in terms of enantiomeric excess of the obtained product. The substrate scope regarding aryltrifluoromethyl ketones 17 is very broad and irrespective of the electronic and Additionally, heteroaromatic trifluoromethyl ketones and aliphatic trifluoromethyl ketones were also suitable and yielded the corresponding aldol products in moderate to good yields (44-78 %) and enantioselectivities (50-75 % ee).…”
Section: Organocatalytic Asymmetric Decarboxylative Aldol Reactions O...mentioning
confidence: 99%
See 4 more Smart Citations
“…[10] The Song group reported an asymmetric decarboxylative aldol reaction of malonic acid half-thioesters 1 (MAHTs) with trifluoromethyl ketones 17 catalyzed by a cinchonidine derived thiourea catalyst F to give enantioenriched β-CF 3 -β-hydroxy esters 18 (Scheme 9) bearing trifluoromethylated tertiary carbon center in low to excellent yields (3-99 %) and with good to excellent enantioselectivities (50-95 % ee). [11] The authors screened several MAHTs, out of which para-fluorophenyl substituted MAHT was found to be most suitable in terms of enantiomeric excess of the obtained product. The substrate scope regarding aryltrifluoromethyl ketones 17 is very broad and irrespective of the electronic and Additionally, heteroaromatic trifluoromethyl ketones and aliphatic trifluoromethyl ketones were also suitable and yielded the corresponding aldol products in moderate to good yields (44-78 %) and enantioselectivities (50-75 % ee).…”
Section: Organocatalytic Asymmetric Decarboxylative Aldol Reactions O...mentioning
confidence: 99%
“…Chiral β‐CF 3 ‐β‐hydroxy esters are attractive target molecules due to presence of their synthetic equivalency in some marketed drugs [10] . The Song group reported an asymmetric decarboxylative aldol reaction of malonic acid half‐thioesters 1 (MAHTs) with trifluoromethyl ketones 17 catalyzed by a cinchonidine derived thiourea catalyst F to give enantioenriched β‐CF 3 ‐β‐hydroxy esters 18 (Scheme 9) bearing trifluoromethylated tertiary carbon center in low to excellent yields (3–99 %) and with good to excellent enantioselectivities (50–95 % ee) [11] . The authors screened several MAHTs, out of which para ‐fluorophenyl substituted MAHT was found to be most suitable in terms of enantiomeric excess of the obtained product.…”
Section: Organocatalytic Asymmetric Decarboxylative Aldol Reactions O...mentioning
confidence: 99%
See 3 more Smart Citations